Factors associated with delayed time to adjuvant chemotherapy in stage III colon cancer - Chan, Arlene; Woods, R.; Kennecke, H.; Gill, S. (Multimed Inc., 2014)
Background Adjuvant chemotherapy started more than 56 days after colon cancer resection has been associated with lesser overall survival among patients with stage iii colon cancer. The objective of the present population-based study was to determine, in referred patients with resected stage iii colon cancer, factors associated with delayed time to adjuvant chemotherapy (ttac), defined as more than 56 days from the date of surgery. Methods Eligible patients had been diagnosed with stage iii colon cancer and had received at least 1 cycle of adjuvant chemotherapy at one of the four regional cancer treatment sites during 2008-2009. Prognostic and treatment information was prospectively collected through the BC Cancer Agency's GI Cancers Outcomes Unit, and Charlson comorbidity score was retrospectively determined by chart review. Chi-square and Wilcoxon rank-sum tests were used to measure associations between the timing of adjuvant chemotherapy and select prognostic and treatment variables. Results Median ttac from surgery for the 395 included patients was 58 days, with 54% of the patients receiving adjuvant chemotherapy beyond the recommended 56 days. On multivariate analysis, only treatment at the highest-volume site was independently associated with delayed ttac. Comorbidity index, age, performance status, T stage, tumour location, and oral chemotherapy (compared with intravenous) were not independently associated with delayed ttac. Delays were observed during each interval associated with the patient's transition from surgery to first cycle of adjuvant chemotherapy. Conclusions More than half the patients failed to receive adjuvant chemotherapy within the recommended ttac of 56 days. Delayed ttac was associated with processrelated delays rather than with patient- or diseaserelated factors. Efforts to improve timely referral, triage of consultations, and chemotherapy wait lists are required. © 2014 Multimed Inc.